2020
DOI: 10.1016/j.ijid.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Duration of viral shedding in asymptomatic or mild cases of novel coronavirus disease 2019 (COVID-19) from a cruise ship: A single-hospital experience in Tokyo, Japan

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is the cause of novel coronavirus disease 2019 (COVID-19), was first reported in Wuhan, China, and now has spread across the world as a global pandemic. The propagation from asymptomatic polymerase chain reaction (PCR)-positive individuals represents a complicating factor in the efforts to control the COVID-19 pandemic. We examined the course of PCR assays and the duration of viral shedding in 23 asymptomatic or mild COVID-19 patients from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 15 publications
2
37
0
1
Order By: Relevance
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…In this study, the mean days to negative RT-PCR was 13.6 for asymptomatic and 16.9 for symptomatic patients. Previous studies showed that the median duration of viral shedding was 19 days (range, 6–37 days) from initial viral detection in 23 patients with mild or no symptoms [ 52 ]. Another study showed that more than one month lapsed prior to achieving PCR negativity in asymptomatic patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may require considering prolonged SARS-CoV-2 shedding in asymptomatic or mild cases and recurrence of viral shedding [52]. Data from 68 patients revealed a significantly longer duration of viral shedding from sputum specimens (34 days) than nasopharyngeal swabs (19 days) [53].…”
Section: Discussionmentioning
confidence: 99%